Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Kinerja Karyawan - Doni Saputra; Mahfudiyanto Mahfudiyanto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This research aims to determine the influence of organizational culture and work environment on the performance of CV employees. Gresik Panorama. The method used in this research is a quantitative research method and uses a causal or cause-and-effect approach. The total sample was 50 employees using saturated sampling techniques. Data collection techniques use questionnaires. Data analysis takes the form of validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test, and R2 test. The results of this research show that (1) Organizational Culture influences CV Employee Performance. Panorama Gresik calculated t value 5.224 > t table value 0.278, (2) The work environment has no effect on CV employee performance. Panorama Gresik calculated t value 1.641 > t table value 0.278, (3) Organizational Culture and Work Environment simultaneously influence the performance of CV employees. Panorama Gresik calculated F value 32.133 > table F value 3.19.